Program Planner Dignity and Negotiation in Collaborative Projects - Baldwin, Cheryl K.; Magnuson, Doug (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2022)
In this qualitative interpretivist study, we investigated the types of interactions and negotiations that supported or constrained adult education program planners’ capacity to act, conceptualized as dignity. Data were drawn from interviews with 14 program planners working in collaborative partnerships in U.S. underperforming urban schools. Planner dignity is supported by practice-focused relationships, jointly developing new practices, and program success. Dignity is constrained by organizational hierarchy, unmanageable daily expectations, and ineffective feedback mechanisms causing distance between planners and fracturing the planning table. Dignity affirmation or constraint affect planner uncertainty regarding access to students and resources, control over one’s time, and accountability. Social conditions also affect the quality of interactions. Individualistic and competitive orientations constrain dignity and impede negotiation practices. Co-operative goal orientations support bargaining and consultative problem-solving negotiations; however, these were less common. Findings advance understanding of interactions that underlie and evolve effective negotiation.